2019
DOI: 10.1002/mus.26431
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitic neuropathy: Comparison of clinical predictors with histopathological outcome

Abstract: Introduction:To improve diagnostic accuracy, in this study we compared prebiopsy clinical parameters with subsequent pathological confirmation of peripheral nerve vasculitis. Methods: Clinical, laboratory, and neurophysiological parameters were analyzed for consecutive patients referred for nerve biopsy with suspected vasculitis. Patients were assigned pathological categories of definite, probable, possible, or absent vasculitis using validated guidelines. Patients with definite or probable vasculitis were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
6
16
0
3
Order By: Relevance
“…In our study, the characteristics of peripheral neuropathy in PAN patients are consistent with asymmetric axonal neuropathy that has a predilection for the lower extremities, affects distal limbs more severely than proximal, and involves both motor and sensory nerves. Previous studies have shown that sensorimotor abnormalities on NCS and the presence of a pure axonal neuropathy were most consistent with pathologically con rmed vasculitis 25,26 , which is consistent with our ndings. The lower limb is the most susceptible to nerve injuries in PAN patients, since the high frequent of disease onset rate appeared at lower limb in the clinical data and the abnormal amplitudes of peroneal and sural nerve were detected in NCS.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the characteristics of peripheral neuropathy in PAN patients are consistent with asymmetric axonal neuropathy that has a predilection for the lower extremities, affects distal limbs more severely than proximal, and involves both motor and sensory nerves. Previous studies have shown that sensorimotor abnormalities on NCS and the presence of a pure axonal neuropathy were most consistent with pathologically con rmed vasculitis 25,26 , which is consistent with our ndings. The lower limb is the most susceptible to nerve injuries in PAN patients, since the high frequent of disease onset rate appeared at lower limb in the clinical data and the abnormal amplitudes of peroneal and sural nerve were detected in NCS.…”
Section: Discussionsupporting
confidence: 93%
“…Not surprisingly, demyelinating and normal nerve conduction studies, cerebrospinal fluid pleocytosis, and pure motor syndromes are very rarely associated with vasculitis on nerve biopsy. These findings are certainly in line with previously published literature, and this approach can serve as a guide for deciding which patients should have a nerve biopsy …”
supporting
confidence: 88%
“…These findings are certainly in line with previously published literature, and this approach can serve as a guide for deciding which patients should have a nerve biopsy. 1 Overall, nerve biopsy is being performed less frequently in modern medical practice, but Nathani et al point to a key area (vasculitis) in which nerve pathology results are still very useful for obtaining a diagnosis. Given the high-risk and extended treatment regimens necessary for successful treatment of necrotizing large arteriole vasculitis, a degree of certainty regarding the diagnosis is important.With recent advances in other areas of neuromuscular medicine (such as imaging and genetics), we have encountered some neuromuscular specialists who believe that nerve biopsy is becoming obsolete and argued that it should be used primarily as a research tool.…”
mentioning
confidence: 99%
“…Optimal outcomes with nerve biopsy requires appropriate selection of patients, 153 nerves and neuropathology techniques. No guidelines exist to inform patient selection for nerve biopsy.…”
Section: Methodsmentioning
confidence: 99%